2017
DOI: 10.1111/jeu.12387
|View full text |Cite
|
Sign up to set email alerts
|

The First Isolation and Characterisation of the Protist Labyrinthula sp. in Southeastern Australia

Abstract: As a result of anthropogenic influences and global climate change, emerging infectious marine diseases are thought to be increasingly more common and more severe than in the past. The aim of our investigation was to confirm the presence of Labyrinthula, the aetiological agent of the seagrass wasting disease, in Southeastern Australia and provide the first isolation and characterisation of this protist, in Australia. Colonies and individual cells were positively identified as Labyrinthula using published descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Labyrinthulomycetes are the most ubiquitous and widespread straminipilan protists in oceans with a total of 13 known genera and 30 described species so far [10]. They have been isolated, using the direct-plating and pollen-baiting methods, from various habitats (e.g., marine seawater, estuarine water, sediments, decaying mangrove leaves, and senescent macroalgae) [11,12,13,14,15,16]. Yet, the majority of the species described are isolated from only a limited number of coastal regions, for example, Japan [17], Australia [12,18], Canada [19], India [20,21,22], Chile [11], China [23], Malaysia [24,25], and Thailand [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labyrinthulomycetes are the most ubiquitous and widespread straminipilan protists in oceans with a total of 13 known genera and 30 described species so far [10]. They have been isolated, using the direct-plating and pollen-baiting methods, from various habitats (e.g., marine seawater, estuarine water, sediments, decaying mangrove leaves, and senescent macroalgae) [11,12,13,14,15,16]. Yet, the majority of the species described are isolated from only a limited number of coastal regions, for example, Japan [17], Australia [12,18], Canada [19], India [20,21,22], Chile [11], China [23], Malaysia [24,25], and Thailand [26].…”
Section: Introductionmentioning
confidence: 99%
“…Although the labyrinthulids group are important ecologically, there is no formal estimate of their culturable diversity. So far, only a few studies have reported on the isolation of labyrinthulids [15,27]. On the contrary, the group thraustochytrids has gained significant attention of researchers because of their biotechnological potential [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent SSU rDNA analyses and ITS strain demarcation indicate a huge variety and a large number of undescribed species in Labyrinthula (Sullivan et al. ). Haplogroup compositions based on TCS haplotype networks from our study generally coincide with haplogroups previously delimited by the methods of neighbor joining and the maximum likelihood (Martin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Much of this work has been done in Z. marina and other North American and European species. However, more recently, research has emerged on the biology and ecology of Labyrinthula at the global level where researchers have investigated phylogeny and global trends in pathogenicity of Labyrinthula (Martin et al, 2016), including the most recent work describing isolation, phylogeny (Sullivan et al, 2016) and pathogenicity (Trevathan-Tackett et al, unpublished) of Labyrinthula spp. in the southern hemisphere.…”
Section: History Of Seagrass Disease Researchmentioning
confidence: 99%